Bioplateau for the purification of water bodies from heavy metals - Lapan, O.V.; Mikhyeyev, O.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
A mobile bioplateau design for the purification of water bodies from heavy metals has been developed, where higher land plants are used as the biotic component. To construct a bio plateau, chemically inert floating materials are used as the substrate granular foam, on whose top the seeds of higher terrestrial plants are placed. The constructed bioplateaux on the 9th day of incubation were placed into tanks with a solution of heavy metals to study the cleaning efficiency of timothy in the aquatic environment. For the study of the influence of chro mium (VI) on growth parameters of timothy, the bioplateaux were placed in desiccators with tap water, which additionally introduced potassium bichromate. The measurements of the length of the stems and roots were carried out at the 8th and 13th days of incubation of the bioplateau in the solution. The efficiency of the proposed hydrophytic structure with timothy plants meadow with respect to chromium (VI), cadmium ions (II) and zinc (II) is shown. A study of the effect of chromium (VI) on the growth parameters of timothy grass plants is conducted.